Induction of Erythrocyte Membrane Blebbing by Methotrexate-Induced Oxidative Stress. Issue 2 (4th June 2022) - Sattar, Tayyba; Jilani, Kashif; Parveen, Khalida; Mushataq, Zahid; Nawaz, Haq; Khan, Maham Abdul Bari
Methotrexate (MTX) is a common chemotherapeutical agent and folate antagonist with reported apoptotic activity in nucleated cells. The presented research work was planned to investigate the eryptotic effects of methotrexate after the exposure of erythrocytes to therapeutical doses (10–15 μM) of methotrexate. Eryptosis and the role of calcium in the stimulation of membrane blebbing were evaluated through the determination of mean cell volume. Oxidative stress induced by methotrexate (10–15 μM) was determined by antioxidative enzyme activities. Cytotoxic activity against human erythrocytes was examined through hemolysis assay. Exposure of erythrocytes to methotrexate results in significant reduction of superoxide dismutase, catalase, and superoxide dismutase activities at 10 and 15 μM in comparison to the untreated cells. Erythrocytes mean cell volume (MCV) was increased after 48 hours exposure of erythrocytes to methotrexate (10 μM). Significantly increased hemolysis percentage was observed at 10 μM after 48 hours incubation of erythrocytes with methotrexate. The results of the study suggested that the therapeutical doses (10–15 μM) of methotrexate may lead to increase in eryptotic and hemolytic activity of erythrocytes through free radical generation and subsequent calcium entry.